2011
DOI: 10.1007/s10561-011-9250-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical grade cultivation of human Schwann cell, by the using of human autologous serum instead of fetal bovine serum and without growth factors

Abstract: Clinical grade cultivation of human schwann cell by the utilization of human autologous serum instead of fetal bovine serum, and also avoiding any growth factors, can increase safety level of this procedure in cases of clinical cell transplantation. The aim of this study was demonstration of the feasibility of clinical grade schwann cell cultivation. In this experimental study after obtaining consent from close relatives we harvested 10 sural nerves from brain death donors and then cultured in 10 seperated cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Investigators in Iran reported two studies: the first with four patients with chronic thoracic SCI transplanted with autologous Schwann cells [5] followed for 1 year and a second report of 33 patients with 2-year follow-up [6]. They described a method to cultivate human Schwann cells using initial serum starvation followed by exposure to autologous serum without growth factors [8], arguing that this technique may be safer than the use of artificial mitogens. A Chinese study enrolled six patients with chronic SCI and reported their results after following the patients for 5 years.…”
Section: Introductionmentioning
confidence: 99%
“…Investigators in Iran reported two studies: the first with four patients with chronic thoracic SCI transplanted with autologous Schwann cells [5] followed for 1 year and a second report of 33 patients with 2-year follow-up [6]. They described a method to cultivate human Schwann cells using initial serum starvation followed by exposure to autologous serum without growth factors [8], arguing that this technique may be safer than the use of artificial mitogens. A Chinese study enrolled six patients with chronic SCI and reported their results after following the patients for 5 years.…”
Section: Introductionmentioning
confidence: 99%
“…To address these problems, various alternatives have been explored by several investigators to maintain proliferation and differentiation of MSCs. Among these are human blood derived alternatives such as autologous human serum (autoHS), allogenic Human Serum (alloHS) [25], human platelet lysates [26], umbilical cord blood serum [27] and autologous plasma derived from bone marrow (AP) [28]. There are several investigations on the efficacy of alloHS, autoHS and AP as an option to FBS for BM-MSCs culture [29,30] but none for DPSCs.…”
Section: Introductionmentioning
confidence: 99%
“…When there is no alternative to research-grade reagents, the animal origin could be used if the manufacturer officially confirms their compliance with GMP regulations. We previously reported the clinicalgrade cultivation and banking of human Schwann cells, human fetal liver-derived mesenchymal stem cells, and human adipose tissue-derived mesenchymal stem cells (19,35,36). In the current study, in order for clinical-grade fibroblasts establishment, according to the Stringent Ethical guidelines, informed consent was obtained from the donor.…”
Section: Discussionmentioning
confidence: 99%
“…Present relevant guidelines focus on progression, production, quality control, and non-clinical and clinical advances in cellular therapy (18). Therefore, when cell preparation complies with GMP regulations, the safety and quality of the final product will be increased (19). To achieve this aim, safe and pure reagents must be used during the entire cell production processes and research-grade reagents must be replaced by valid GMP-grade materials, to extend possible (20).…”
Section: Introductionmentioning
confidence: 99%